Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's match the steps in solving the equation [tex]\(3(x-4)+5=2x-2(3-x)\)[/tex] with the appropriate reasons.
Steps:
1. [tex]\(3(x-4)+5 = 2x-2(3-x)\)[/tex]
2. [tex]\(3x-12+5 = 2x-6+2x\)[/tex]
3. [tex]\(3x-7 = 4x-6\)[/tex]
4. [tex]\(-7 = x-6\)[/tex]
5. [tex]\(x = -1\)[/tex]
Reasons:
1. given
2. distributive property
3. combine like terms
4. subtraction property of equality
5. addition property of equality
Putting them together:
[tex]\[ \begin{array}{ll} 3(x-4)+5=2 x-2(3-x) & \quad \text{given} \\ 3 x-12+5=2 x-6+2 x & \quad \text{distributive property} \\ 3 x-7=4 x-6 & \quad \text{combine like terms} \\ -7=x-6 & \quad \text{subtraction property of equality} \\ x = - 1 & \quad \text{addition property of equality} \\ \end{array} \][/tex]
Therefore, the correctly matched steps and reasons are:
1. [tex]\( 3(x-4)+5=2x-2(3-x) \quad \longrightarrow \)[/tex] [tex]\( \text{given} \)[/tex]
2. [tex]\( 3x-12+5=2x-6+2x \quad \longrightarrow \)[/tex] [tex]\( \text{distributive property} \)[/tex]
3. [tex]\( 3x-7=4x-6 \quad \longrightarrow \)[/tex] [tex]\( \text{combine like terms} \)[/tex]
4. [tex]\( -7=x-6 \quad \longrightarrow \)[/tex] [tex]\( \text{subtraction property of equality} \)[/tex]
5. [tex]\( x = -1 \quad \longrightarrow \)[/tex] [tex]\( \text{addition property of equality} \)[/tex]
Steps:
1. [tex]\(3(x-4)+5 = 2x-2(3-x)\)[/tex]
2. [tex]\(3x-12+5 = 2x-6+2x\)[/tex]
3. [tex]\(3x-7 = 4x-6\)[/tex]
4. [tex]\(-7 = x-6\)[/tex]
5. [tex]\(x = -1\)[/tex]
Reasons:
1. given
2. distributive property
3. combine like terms
4. subtraction property of equality
5. addition property of equality
Putting them together:
[tex]\[ \begin{array}{ll} 3(x-4)+5=2 x-2(3-x) & \quad \text{given} \\ 3 x-12+5=2 x-6+2 x & \quad \text{distributive property} \\ 3 x-7=4 x-6 & \quad \text{combine like terms} \\ -7=x-6 & \quad \text{subtraction property of equality} \\ x = - 1 & \quad \text{addition property of equality} \\ \end{array} \][/tex]
Therefore, the correctly matched steps and reasons are:
1. [tex]\( 3(x-4)+5=2x-2(3-x) \quad \longrightarrow \)[/tex] [tex]\( \text{given} \)[/tex]
2. [tex]\( 3x-12+5=2x-6+2x \quad \longrightarrow \)[/tex] [tex]\( \text{distributive property} \)[/tex]
3. [tex]\( 3x-7=4x-6 \quad \longrightarrow \)[/tex] [tex]\( \text{combine like terms} \)[/tex]
4. [tex]\( -7=x-6 \quad \longrightarrow \)[/tex] [tex]\( \text{subtraction property of equality} \)[/tex]
5. [tex]\( x = -1 \quad \longrightarrow \)[/tex] [tex]\( \text{addition property of equality} \)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.